Effective Treatment of Acute Wrist Pain in a Competitive Weightlifter Using Tendon Traction Point-Focused Dextrose Injections: A Case Report - Yang CJ; Park SH; Lee JH; Kim TS; Seong JW (International Medical Case Reports Journal)
Cheol-Jung Yang,1,2 Sin-Hye Park,3 Je Hun Lee,2,4 Taek-Sung Kim,2 Jeong-Won Seong1 1Department of Orthopedic Surgery, Borntouch Orthopaedic Clinic, Seoul, Republic of Korea; 2Department of Sports, Korea National Sport University, Seoul, Republic of Korea; 3Department of Food Science and Nutrition, Korean Institute of Nutrition, Hallym University, Chuncheon-si, Gangwon State, Republic of Korea; 4Korea Institute for Applied Anatomy, College of Sports Science, Korea National Sport University, Seoul, Republic of KoreaCorrespondence: Cheol-Jung Yang, Department of Orthopedic Surgery, Borntouch Orthopaedic Clinic, Godeok-ro 262, Gangdong-gu, Seoul, 05269, Republic of Korea, Tel +82-02-442-0087, Email cjyangosdr@gmail.comAbstract: Wrist pain is common among athletes, particularly weightlifters, who perform repetitive high-intensity movements like the snatch and clean and jerk. Conventional treatments, including NSAIDs, corticosteroids, and physical therapy, often provide only symptomatic relief. This case report highlights effective management of acute wrist pain in a competitive weightlifter using Tendon Traction Point (TTP)-focused dextrose injections. A 23-year-old weightlifter presented with wrist pain persisting for two weeks despite prior treatments. Tenosynovitis of the extensor digitorum communis (EDC) and extensor carpi radialis brevis (ECRB) tendons was confirmed by ultrasound. After four injections of 5% dextrose into identified TTPs, the patient’s Visual Analog Scale (VAS) score improved from 7 to 1. The treatment relieved pain and enabled the athlete to return to competition. This report demonstrates that TTP-focused dextrose injections offer a rapid, effective, and non-invasive solution for athletes with tendon overuse pain, presenting a promising alternative to traditional therapies and supporting functional recovery.Keywords: wrist pain, weightlifter, extensor digitorum communis, extensor carpi radialis brevis, tendon traction point